2008
DOI: 10.1080/07434610802109915
|View full text |Cite
|
Sign up to set email alerts
|

Moving Targets: The Effect of Animation on Identification of Action Word Representations

Abstract: This study examined the conditions under which action representations - presented in both static and dynamic formats - were most readily identified. Preschoolers without disabilities selected graphics corresponding to a spoken word from a computerized four-choice array. Although pre-tests confirmed that the children had all of the stimulus words in their lexical repertoires, their demonstration of that knowledge when the stimuli were presented in graphical form was less robust. The children were generally more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 42 publications
0
20
2
Order By: Relevance
“…For example, based on visual neuroscience research, Jagaroo and Wilkinson (2008) proposed that we may be able to exploit movement (animation) to highlight conceptual relationships (such as those enacted in verbs or prepositions). Mineo, Peischl, and Pennington (2008) found that animation did indeed positively impact children's understanding of action concepts. Shane and colleagues applied this research to develop a new set of AAC symbols, the Autism Language Program (ALP) Animated Graphics Set.…”
Section: Representations Of Language Concepts For Children With Ccnmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, based on visual neuroscience research, Jagaroo and Wilkinson (2008) proposed that we may be able to exploit movement (animation) to highlight conceptual relationships (such as those enacted in verbs or prepositions). Mineo, Peischl, and Pennington (2008) found that animation did indeed positively impact children's understanding of action concepts. Shane and colleagues applied this research to develop a new set of AAC symbols, the Autism Language Program (ALP) Animated Graphics Set.…”
Section: Representations Of Language Concepts For Children With Ccnmentioning
confidence: 95%
“…As a result, children with CCN may fall further and further behind their peers in their semantic development, at least in part, due to system constraints, specifically the learning demands imposed by traditional AAC symbols. Mineo et al (2008) explained: "We may underestimate an individual's underlying competence if we fail to use appropriate representations as the means to tap into and evaluate this competence, and we may inhibit learning if we use inappropriate representations as the scaffold on which to build." (p. 162).…”
Section: Representations Of Language Concepts For Children With Ccnmentioning
confidence: 98%
“…Although some limited sets of animated symbols have been available for many years (Zangari et al 1994), they have received limited usage and there has been no investigation of their efficacy conducted until recently. In a recent study, Mineo et al (2008) reported that non-disabled preschoolers identified symbols for actions better when they were animated rather than static. Recently, completed a study with nondisabled preschoolers across three age groups to determine the effects of animation on guessing, naming, and identifying graphic symbols for verbs and prepositions.…”
Section: Using Technology To Improve Graphic Representations Of Diffimentioning
confidence: 98%
“…Findings suggest that cartoon animations of action words are easier to recognize than static icons [10,11]; black-and-white video is easier to recognize than animated line drawings [8]; and animation accelerates learning of static icons [4]. Finally, work by Light & McNaughton [6] suggests that personalization and "just-in-time" capture of language concepts should be key priorities for future AAC systems.…”
Section: Related Workmentioning
confidence: 92%